A modified molecular framework derived highly efficient Mn–Co–carbon cathode for a flexible Zn–air battery. Issue 84 (9th October 2017) - Cheng, Hui; Chen, Jun-Min; Li, Qi-Jia; Su, Chang-Yuan; Chen, An-Na; Zhang, Jia-Xuan; Liu, Zhao-Qing; Tong, Yexiang
Abstract : Advanced Co–Mn bimetallic nanoparticles are decorated on high conductivity nitrogen doped carbon nanotubes to serve as the efficient oxygen-catalyst. Abstract : A controllable Co doping strategy is introduced to significantly activate more catalytic sites for Mn-based materials and anchor Co–Mn nanoparticles on the N-doped carbon nanotube (N-CNT) substrates. The as-synthesized CoMn2 O4 /N-CNTs exhibit excellent ORR catalytic performance with large limited current density and positive half-wave potential, even outperforming the Pt/C catalysts. The outstanding ORR activity allows the CoMn2 O4 /N-CNTs to directly serve as the cathode electrode in a liquid/solid state Zn–air battery, demonstrating large power density and robust stability.